7 - Renaissance africaine : l’environnement juridique - Diakhaté, Maty BB-Laye (Africa Development, 2021)
Community life necessarily requires rules and regulations. Therefore, every human settlement generates from within a mechanism to govern relationships between individuals related to culture which is called: law. This means that law is an unquestionable cultural feature. We can also say that this is one of the most dynamic elements. Actually, law is also crucial to culture because it is an emanation of culture. There are a number of interactions that closely bind law to culture... When it comes to the theme of African Renaissance, law necessarily comes into play as a cultural feature and engine. Before positing that the African renaissance facilitates the emergence of legal systems in line with the cultures of Africa there is a gap that necessarily needs to be bridged. In fact, law being primarily a human phenomenon, each group breeds its own law, codes, its solidarity mechanisms and this applies to Africa. This also means that Africa is a socio-cultural entity although markedly diverse. These cultural, linguistic, ethnic diversities and therefore legal, that characterize it are not exclusive of common principles capable of supplying the foundations of endogenous legal systems. Thus, taken from a legal standpoint, the programmatic content of the African renaissance could be defined based on a set of historical, sociological and economic data. This calls for a mobilization of sources and multidisciplinary resources and conceptualization efforts. It is in this end that hereby article raises some issues and gives room to discussions.